Stock Control of Enduro Matic Oil Products Using the Economic Order Quantity (EOQ) Method at DRMS#71 Motor Workshops - Muhammad Rizqi Rahmatullah; Muhamad Sodiq (PT FORMOSA CENDEKIA GLOBAL, 2022)
Problems with economical ordering, safety stock, and when to reorder (ROP) within one year. The results of the study used the EOQ method to purchase 1,470 bottles of goods with an order frequency of 1 time per year. Based on the analysis using the EOQ method, it can maintain the stability of the customer request process. With EOQ you can also reduce the cost of saving from Rp. 1,360,000 to Rp. 1,176,000.-.